IMPORTANCE OF LIPIDS IN THE CELL, SIMPLE AND COMPLEX LIPIDS, CLASSIFICATION (ResearchJet Journal of Analysis and Inventions, 2021)
The role of lipids in the cell, simple and complex lipids, classification.